Atherogenic Lipid Ratios Related to Myeloperoxidase and C-Reactive Protein Levels in Psychotic Disorders - Reponen, Elina J.; Dieset, Ingrid; Tesli, Martin; Mørch, Ragni H.; Aas, Monica; Vedal, Trude S. J.; Haug, Elisabeth; Drange, Ole Kristian; Steen, Nils Eiel; Hope, Sigrun; Szabo, Attila; Gohar, Sherif M.; et al. (Frontiers in Psychiatry, 2020)
Background. Cardiovascular disease (CVD) is a major cause of premature death in patients with psychotic disorders, where dyslipidemia occurs frequently. In the pathogenesis of these serious mental disorders, a low-grade inflammation seems to be a possible contributor. Concurrently, systemic inflammation and its interplay with dyslipidemia is a central driver in the pathogenesis of CVD. We hypothesize that evaluation of atherogenic lipid ratios together with inflammatory markers reflecting different inflammatory pathways with relevance for atherogenesis, could give novel information on immune-related mechanisms involved in early CVD risk in patients with psychotic disorders. Methods. As a measure for CVD risk we calculated atherogenic lipid ratios using established sex-specific cut-offs: Total cholesterol/high-density lipoprotein; HDL-c (TC/HDL) and triglyceride/HDL-c (TG/HDL) were evaluated in 571 schizophrenia (SCZ) and 247 bipolar disorder (BD) patients, and in 99 healthy controls (HC). In addition, as a measure of low-grade inflammation, we measured fasting plasma levels of nine stable atherogenic inflammatory markers in patients (SCZ, BD) and in HC. The elevated inflammatory markers and CVD risk in patients, as reflected by TC/HDL and TG/HDL, were further assessed in multivariable analyses adjusting for comorbid cardio-metabolic risk factors. Results. A markedly higher proportion (26-31%) of patients had increased TC/HDL and TG/HDL ratios compared with HC. Plasma levels of high-sensitivity C-reactive protein (hs-CRP) and myeloperoxidase (MPO) were higher (p<0.05, p<0.001) in patients with psychotic disorders than in HC, and hs-CRP and MPO were independently associated with atherogenic lipid ratios in the multivariable analyses. Conclusions. Our findings suggest that low-grade inflammation and abnormal neutrophil activation may cause increased CVD risk in patients with psychotic disorders. These mechanisms should be further examined to determine the potential for development of novel risk evaluation strategies.